IMPLEMENTASI MATRIKS ATAS GELANGGANG Z_p⨁Z_q⨁Z_r PADA KRIPTOGRAFI CIPHER HILL - Ro'uf, Ikhsan Abdul; Solikhin, Mukhammad; Aeli, Lita Wulandari; Pahrany, Andi Daniah; Hasanah, Irmatul (Jurnal Kajian Matematika dan Aplikasinya (JKMA), 2023)
Cryptography is a method for securing data or information from data leaks. In cryptography, there are two important processes, namely, the encryption and decryption processes. Encryption is the process of changing plaintext into ciphertext using certain keys and algorithms, while decryption is the process of changing ciphertext into plaintext using keys and algorithms that match the encryption. There is a cryptosystem that is well known, namely Cipher Hill. Cipher Hill uses a square matrix for the encryption and decryption process. In this research, an mxn-sized matrix will be used over the Direct Sum ring Z_p⨁Z_q⨁Z_r to expand the Cipher Hill algorithm. The author also uses the pseudoinverse concept to find the inverse of an mxn matrix. By using an mxn matrix, the encryption results allow the length of the plaintext to be different from the length of the ciphertext.Keywords: Cipher Hill, Cryptography, Decryption, Encryption, Direct Sum, Pseudoinvers